Ecosystem services in Patagonia: A synthesis and future directions. - Nahuelhual, Laura; Martínez Pastur, Guillermo José; Peri, Pablo Luis (Springer, 2021)
In this closing chapter, we provide a synthesis of the Patagonian ecosystems and ES that were more frequently addressed in the preceding chapters, along with the main transformations and associated drivers. We also synthetize the research gaps and the recommendations provided by the authors  and delineate future directions for ES research in Patagonia. Natural and human-induced drivers have modeled and remodeled Patagonian landscapes continuously. The chapters in this book describe recent landscape transformations and the major human-derived impacts on biodiversity and provision of ecosystem services (ES). The chapters also discuss implications of these changes for human well-being and provide recommendations for decision-making.